CONSTRUCTING NATIONAL IDENTITY: A CRITICAL DISCOURSE ANALYSIS OF INDONESIA'S WORLD CUP ASPIRATIONS IN THE JAKARTA POST - Hafiza Saumi Ramadilla; Halimah Br. Surbakti; Gerardo Ryan Tuah Pratama Purba (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study aims to conduct a Critical Discourse Analysis (CDA) of the article "Indonesia closer to dream of World Cup," published by The Jakarta Post on June 12, 2024. Employing Teun A. van Dijk’s CDA framework, this research seeks to uncover the underlying themes, social cognitions, and contextual elements that shape the narrative presented by the media regarding Indonesia’s aspiration to host the FIFA World Cup. The Jakarta Post's coverage is of particular interest as it reflects and potentially influences national sentiments and perceptions concerning Indonesia's international standing and capabilities. The findings of this study indicate that The Jakarta Post employs a strategic use of language to construct a positive and aspirational narrative around Indonesia’s World Cup bid. The use of optimistic language, motivational rhetoric, and authoritative quotes creates a compelling vision of national progress and international recognition. This narrative not only reflects the country's ambitions but also serves to mobilize public support and foster a sense of collective identity and purpose. This s study contributes to the field of media studies and critical discourse analysis by providing insights into the interplay between media, society, and national identity. It underscores the power of media narratives in shaping public perception and mobilizing collective action towards national goals. The application of van Dijk’s CDA framework provides a robust analytical tool for examining how discourse structures reflect and shape power relations, ideologies, and social structures within a specific cultural and historical context. This research thus offers valuable perspectives on the role of media in constructing and disseminating discourses that influence societal values and ideologies, particularly in the context of major international events such as the FIFA World Cup.